Pharmacological prevention of post-traumatic stress disorder and acute stress disorder: a systematic review and meta-analysis. (May 2015) - Sijbrandij, Marit; Kleiboer, Annet; Bisson, Jonathan I; Barbui, Corrado; Cuijpers, Pim
Summary: Background: An increasing number of studies have investigated the pharmacological prevention of post-traumatic stress disorder (PTSD) and acute stress disorder (ASD). This is the first systematic review to examine the effects of pharmacotherapies (eg, β blockers, hydrocortisone, and selective serotonin re-uptake inhibitors) given within the first month after a traumatic or aversive event to prevent PTSD or ASD compared with no pharmacotherapy or placebo control. Methods: A systematic literature search in PubMed, PsycINFO, Embase, and the Cochrane database of randomised trials was done. Studies included randomised controlled trials, controlled clinical trials, and cohort studies; their overall quality was low to moderate. We computed the pooled incidence risk ratio (IRR): the risk of incidence of PTSD or ASD in the pharmacotherapy groups relative to the incidence of PTSD or ASD in the control groups. Additionally, we computed Hedges' g effect sizes for PTSD or ASD continuous outcomes. Findings: 15 studies met inclusion criteria (1765 individuals). Pharmacotherapy was more effective in preventing PTSD or ASD than placebo or no intervention (14 studies, 1705 individuals, IRR 0·65, 95% CI 0·55–0·78; number needed to treat 11·36), although no effect was found when only randomised controlled trials were included (ten studies, 300 individuals, IRR 0·69, 95% CI 0·40–1·21). Hydrocortisone showed a large effect in reducing the risk of PTSD (five studies, 164 individuals, IRR 0·38, 95% CI 0·16–0·92). Interpretation: No firm evidence was found for the efficacy of all early pharmacotherapies in the prevention of PTSD or ASD, but hydrocortisone reduced the risk of developing PTSD. The small number of studies and their limited methodological quality cast uncertainty about the effects. Funding: None.